(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The paper deals with various aspects of marketing such as meaning, definitions and activities etc. The study also describes different aspects of marketing of library product & services. It highlights need and importance of marketing of library product & services and skill of the objective present study is to market the Information Center of library product & services in Delhi. In industries it is necessary to market the products to increase sales and gain profits however to create awareness the library services like Information Centres, universities and colleges require promotion and marketing of library and information sector and also point out several role libraries for marketing of library products & services. It describes in detail various products and services in Information Centres in Delhi. finally suggest strategies for promotion of marketing of product & services in library Information Centres in Delhi.